Cancers of the Skin: Proceedings of the 8th World Congress - Dummer, Reinhard (Recent Results in Cancer Research, 2002)
Skin cancer is the most frequent malignancy in humans and its incidence is still increasing. This situation calls for major efforts to manage the disease. Preventive measures must include reduced UV exposure and an enhanced common awareness of skin lesions. Advanced surgical techniques allow safe removal with excellent cosmetic results. In many cases alternative treatment modalities such as radiotherapy, cryosurgery and photodynamic therapy are applicable. The development of optimal sun screens and UV-protective clothes, new tools for early diagnosis of malignant lesions including videomicroscopy, improved evaluation of biopsy material and new treatment schemes will contribute to better patient care. New developments in therapy including pegylated interferons, cytokine-inducing molecules, monoclonal antibodies and vaccination approaches using peptides, dendritic cells, viruses or nDNA give hope for well-tolerated and efficient treatments